Gramicidin ion channels in a lipid bilayer supported on polyelectrolyte multilayer films: An electrochemical impedance study - Diamanti, Eleftheria (2017)
Supported membranes on polymer cushions are of fundamental interest as models for cell membranes. The use of polyelectrolyte multilayers (PEMs) assembled by the layer by layer (LbL) technique as supports for a bilayer allows for easy integration of the lipid bilayer on surfaces and devices and for nanoscale tunable spacing of the lipid bilayer. Controlling ionic permeability in lipid bilayers supported on PEMs triggers potential applications in sensing and as models for transport phenomena in cell membranes. Lipid bilayers displaying gramicidin channels are fabricated on top of polyallylamine hydrochloride (PAH) and polystyrene sulfonate (PSS) multilayer films, by the assembly of vesicles of phosphatidylcholine and phosphatidylserine, 50:50 M/M, carrying gramicidin (GA). Quartz crystal microbalance with dissipation shows that the vesicles with GA fuse into a bilayer. Atomic force microscopy reveals that the presence of GA alters the bilayer topography resulting in depressions in the bilayer of around 70 nm in diameter. Electrochemical impedance spectroscopy (EIS) studies show that supported bilayers carrying GA have smaller resistances than the bilayers without GA. Lipid layers carrying GA display a higher conductance for K+ than for Na+ and are blocked in the presence of Ca2+.